PENATALAKSANAAN ASUHAN KESEHATAN GIGI DAN MULUT PERIOPERATIF PADA KLIEN AN. R (3 TAHUN) DENGAN KASUS RANULA DI RSUP Dr. HASAN SADIKIN BANDUNG - Tri Agustina; Megananda Hiranya Putri; Nining Ningrum; Irwan Supriyanto; Melita Sylvyana (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Palembang, 2026)
Background: The prevalence of residents in West Java Province who have had dental health problems in the past year for those aged ≥ 3 years has reached 48%. One oral health problem that can reduce quality of life is ranula. Ranula is a cyst of the floor of the mouth that occurs due to damage to the sublingual salivary gland duct or the submandibular duct. Ranula is usually not painful, the most common complaint expressed by clients is a feeling of fullness in the mouth and a raised tongue. The consequences of ranula are not met human needs, including not being free from disease risks and not being met the integrity of skin tissue and mucous membranes in the neck and head. In addition, there is also not being free from pain in the neck and head.Objective: To determine the management of perioperative dental and oral health care for client An. R (3 years old) with a case of ranula at Dr. Hasan Sadikin General Hospital, Bandung.Methods: The management of dental and oral health care includes the stages of assessment, perioperative diagnosis, perioperative planning, perioperative implementation, perioperative evaluation and documentation.,Results: The eight basic needs of the client were fulfilled after perioperative dental and oral health care was carried out on client An. R (3 years old) with a ranula case.Conclusion: The assessment revealed swelling under the tongue (ranula), irritation on the upper tongue, caries on tooth 61, and a plaque score of 25%. Seven basic needs were unmet. The procedures included removal of the ranula using marsupialization under general anesthesia and placement of a composite resin filling on tooth 61, education on anxiety reduction, the causes of ranula and its treatment, and the causes of caries. Oral physiotherapy training on modified bass toothbrushing techniques was also provided.